Strong soldiers, failed revolution the state and military in Burma, 1962-1988 - Nakanishi, Yoshihiro (Kyoto CSEAS series on Asian studies / Center for Southeast Asian studies, Kyoto University, 2013)
General Ne Win's state reformation in the name of the 'Burmese Way to Socialism' contributed to the expansion of the political role of the Myanmar Armed Forces, the 'tatmadaw', but the underlying dynamics of this change remain poorly understood. Drawing on propaganda publications, profiles of the country's political elites, and original documents in Burma's military archives, Yoshihiro Nakanishi offers a fresh look at the involvement of the 'tatmadaw' in Burma's ideological discourse and civil-military relations.